2004
DOI: 10.1111/j.1365-2591.2004.00765.x
|View full text |Cite
|
Sign up to set email alerts
|

A clinical radiographic retrospective assessment of the success rate of single‐visit root canal treatment

Abstract: Seven hundred and sixty-eight single-visit cases, of which 223 presented for a re-examination appointment ranging from 6 months to 4 years from the day of treatment, were considered. Four endodontists provided examinations for both root canal treatment and re-examinations. Clinical and radiographic data were used to form an overall impression of the outcomes for each case at the time of re-examination. Available demographics and treatment information of these 223 cases were compiled for comparison. The number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
1
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 43 publications
7
32
1
6
Order By: Relevance
“…In the molar group, a gap of Ͼ2 mm between the post and the gutta-percha resulted in an unfavorable clinical outcome in all the teeth examined. These results are compatible with the findings of some studies, in which anterior tooth treatment are associated with a more favorable outcome than that of posterior teeth (2,23,29), although not with those of others (25,30). Despite the fact that they dealt with different factors related to the clinical outcome of treatment, it is likely that the anatomy of a multirooted tooth presents a greater challenge for the operator, especially for an undergraduate student.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the molar group, a gap of Ͼ2 mm between the post and the gutta-percha resulted in an unfavorable clinical outcome in all the teeth examined. These results are compatible with the findings of some studies, in which anterior tooth treatment are associated with a more favorable outcome than that of posterior teeth (2,23,29), although not with those of others (25,30). Despite the fact that they dealt with different factors related to the clinical outcome of treatment, it is likely that the anatomy of a multirooted tooth presents a greater challenge for the operator, especially for an undergraduate student.…”
Section: Discussionsupporting
confidence: 91%
“…The position of the tooth in the arch had no significant influence as previously reported in studies regarding other aspects of the clinical outcome of endodontic treatment (29,31).…”
Section: Discussionsupporting
confidence: 46%
“…Minute differences in periapical healing were observed among individuals undergoing single visit and multiple visit root canal treatment and bacterial growth at the second appointment had a significant negative impact on healing of the periapical lesion [4,5]. In addition to this, the clinical efficacy of sodium hypochlorite irrigation in the control of root canal infection is much more than the effectiveness of interappointment calcium hydroxide dressing, in disinfecting the root canal system and treatment outcome, indicating the need to develop more efficient inter-appointment dressings [6,7]. E. faecalis is the most resistant bacterium against calcium hydroxide while sodium hypochlorite is effective against it in both buffered and unbuffered states [8].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown little or no difference in the quality of treatment or success rates between single-and multiple-visit root canal treatment [5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation